Imaging autoclave development for in-situ optical measurement of high temperature aqueous corrosion processes - Wood, P; Duff, J; Marrow, T (2009)
Stress corrosion cracking, oxidation and high temperature aqueous corrosion are life limiting factors in many nuclear process plant components. An Imaging Autoclave has been developed to study these processes, in-situ. The system combines refreshed-loop high temperature and pressure aqueous testing facilities under dynamic loading, with the optical techniques of Digital Image Correlation and Raman Spectroscopy. This paper reports an in-situ study of stress corrosion crack nucleation and growth in Stainless Steel under simulated BWR environments, using digital image correlation. This allows crack opening displacements to be measured that are below normal optical resolution. The aim is to measure crack propagation rates and determine nucleation sites.